Management of heterotopic pregnancy: clinical analysis of sixty-five cases from a single institution - Ge, Feng; Ding, Wei; Zhao, Kun; Qu, Pengpeng (Frontiers in Medicine, 2023)
Objective: This retrospective study aims to analyze the influence of different treatment modalities on viable intrauterine pregnancy and to summarize the clinical features of heterotopic pregnancy (HP) patients. Material and methods: All patients diagnosed with HP between January 2012 and December 2022 in Tianjin Central Obstetrics and Gynecology Hospital were reviewed retrospectively. Results: Sixty-five patients were diagnosed using transvaginal ultrasound (TVS), including two cases of natural pregnancy, seven cases of ovulation induction pregnancy, and 56 cases after in vitro fertilization and embryo transfer (IVF-ET). The gestational age was 50.2 ± 13.0 days at the time of diagnosis. The most frequent manifestations were abdominal pain (61.5%) and vaginal bleeding (55.4%), while 11 patients (16.9%) had no symptoms before the diagnosis. The primary treatment was expectant and surgical management, including laparotomy and laparoscopic surgery. In the expectant management group, four patients were transferred to surgery due to rupture of ectopic pregnancy or ectopic pregnancy mass gradually enlarged. In the surgical management group, 53 patients underwent laparoscopic surgery, and six underwent laparotomy. The laparoscopic group’s mean operation time was 51.3 ± 14.2 min (range: 15–140 min), and the median intraoperative blood loss was 20 mL (range 5–200 mL). In contrast, the laparotomy group’s mean operation time was 80.0 ± 25.3 min (range 50–120 min), and the median intraoperative blood loss was 22.5 mL (range 20–50 mL). Four patients had postoperative abortions. Sixty-one newborns had no birth abnormalities, and no developmental malformations were discovered after a median follow-up of 32 months. Conclusion: Expectant treatment has a high failure rate in HP, and laparoscopic surgery is a safe and effective treatment for removing ectopic pregnancy without increasing the risk of abortion or newborn birth defects.